Regulation of enzymes with identical subunits on the example of Transketolase - Olga N Solovjeva (Open Journal of Analytical and Bioanalytical Chemistry - Peertechz Publications, 2022)
The molecule of transketolase is a dimer with structurally and functionally identical subunits. Its active sites are located in the region of intersubunit contact, which has been shown also for other thiamine enzymes. This leads to the reciprocal influence of active sites in the binding of cofactors and during catalysis. In this review, it is shown that the functional non-equivalence of the active sites of transketolase from Saccharomyces cerevisiae is initially formed upon the binding of the first cofactor, a divalent cation, not thiamine diphosphate, as previously thought. An attempt was made to find the reason for the differences between catalytic measurements and crystallographic data on the possible part-of-the-sites reactivity of the functioning of transketolase. At the same time, the difference in the amplitudes of dichroic absorption during the binding of reversibly and irreversibly splitting substrates has nothing to do with the flip-flop mechanism. It was also shown that with an increase in the concentration of substrates, a sharp decrease in activity occurs, which is explained by a switch from the simultaneous binding of the substrate in two active sites to its alternate binding both in one-substrate and two-substrate reactions. This fact could also be the reason for the rejection of the flip-flop mechanism of catalysis by transketolase. The mechanism may be similar to human transketolase, which may have clinical application.